2014
DOI: 10.1002/hpm.2268
|View full text |Cite
|
Sign up to set email alerts
|

Identifying barriers to move to better health coverage: preferences for health insurance benefits among the rural poor population in La Guajira, Colombia

Abstract: SUMMARYEven though access to health insurance in Colombia has improved since the implementation of the 1993 health reforms (Law 100), universal coverage has not yet been accomplished. There is still a segment of the population under the low-income (subsidized) health insurance policy or without health insurance altogether. The purpose of this research was to identify preferences and behavior regarding health insurance among the subsidized rural population in La Guajira, Colombia, and to understand why that pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…[50] Colombia has also been plagued by underfunding of its subsidized POS component, as well as high rates of informal workers evading their health contributions. Insu cient funding has furthered health inequities [24]. This research has shown that, under these conditions, even with FOSYGA crosssubsidization it does not guarantee the adequate funding.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…[50] Colombia has also been plagued by underfunding of its subsidized POS component, as well as high rates of informal workers evading their health contributions. Insu cient funding has furthered health inequities [24]. This research has shown that, under these conditions, even with FOSYGA crosssubsidization it does not guarantee the adequate funding.…”
Section: Discussionmentioning
confidence: 91%
“…Since inception of Plan Nacer, the low birth weight mortality rates have dropped 9%, while neonatal mortality has fallen 22%. [18,19] [18,19] Central government transferred more than USD 234 million to provinces to fund primary health strategy over SUM\AR [19] HIS is still in development and the country lacks of connectivity across the entire health [18] [19] Strong criticisms about underfunding of SUS [30] Federal spending on healthcare unchanged over 15 year period, slight increase of 0,7% GDP in public health expenditure over 5 year period [21] and still under subsidized causing effect inequalities [24] Labor contributions are based on fixed proportion of the income collected by the government under FOSYGA [ Enhancing the primary care network in Argentina, they introduced preventive health programs, such as those addressing sexually transmitted infections, cardiovascular disease, diabetes, and other chronic conditions. It also increased the number of deliveries attended by skilled healthcare workers, especially for those living below the poverty level.…”
Section: Healthcare Service Deliverymentioning
confidence: 99%
See 1 more Smart Citation
“…The results of the present study show that quality interventions with 18 cases had the least report. While studies on UHC have identi ed the quality of care and regulatory mechanisms for quality as one of the most in uential factors in achieving UHC [33,49,96,97,140]. One of the reasons for low interventions in this dimension could be the over-emphasis of countries on the quantity of services provided and coverage of the majority of the population.…”
Section: Discussionmentioning
confidence: 99%
“…Modern consumers are seeking information about various health insurance types and health care providers(Deloitte, 2008) in order to compare different options and make affiliation decisions(Becker &Zweifel, 2008). In such cases, consumers choose certain organizations based on their evaluation of various attributes of the offer, such as: package of services, high quality of medical services, efficiency of service provision and a waiting period to receive healthcare services, politeness of medical and non-medical staff, family coverage, access to specialists, right to choose a doctor, etc (Amaya et al, 2014)…”
mentioning
confidence: 99%